Fast construction of SARS-CoV-2 associated plasmid library using parallel cloning method - Fan Meng; Jiao Guo; Shan Wang; Changhui Zhang; Xuehui Li; Yanjuan Chen; Qiuli Shi; Liang Shao; Rundong Zhang; Ganggang Wang; Dan Su (Heliyon, 2023)
The COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a significant impact on global health. To address the urgent need for plasmids containing SARS-CoV-2 sequences in research, we have developed a high-throughput FastCloning platform for the construction of associated plasmids. Our platform uses a FastCloning method to construct a plasmid library from 29 ORFs of the virus and 20 commonly used vectors in the lab. The library contains 536 recombinant vectors, with a highly positive clone success rate of 92.4%. Our study provides a rapid and efficient approach to constructing a large plasmid library for SARS-CoV-2 research.